A Popular Post-Yugoslav Cinema: Does it Exist and Why (Not)? - Mitric, Petar; Kolaric, Tamara (Iluminace, 2021)
Building an audience is currently the most challenging task for national film industries in Europe. This article scrutinizes this challenge by focusing on a specific European region - the post-Yugoslav one. Following the disintegration of Yugoslavia, a large joint film market which regularly produced highly successful films was replaced by seven national cinemas. In industry terms, these cinemas operate in a very different context from that of the former Yugoslavia, including no integrative film policy, fragmented territories and audiences. Yet a number of post-Yugoslav films have managed to reach a significant national and/or regional audience.Relying on the concepts of low-brow, middle-brow, high-brow cinema and the ideal European co-production, and using data from the LumierePro database and national film centers, we map out films that achieved success domestically and those that managed to traverse national borders, in order to understand what attracts domestic, regional and (occasionally) international audiences. We also identify the main obstacles to a better box-office of post-Yugoslav films and discuss possible policy steps to remedy them. For this, we analyze film texts, production processes, as well as observational data from two industry events.Our analysis paints a complex picture. While audiences across the region do differ, some thematic and style preferences are shared - a situation that can be harnessed through the development of quality regional ideal European co-productions. But new distribution strategies are needed, together with more scholarly efforts to understand the audiences and their engagement.
Keywords: popular cinema; post-Yugoslav region; ideal European co-productions; Serbia; Croatia; Yugoslavia